1990년대와 2010년대 이후 드라마 자료 분석을 통해 살펴본 네, 예 사용의 변이와 변화 - 장교진(Gyojin Jang); 신지영(Jiyoung Shin) (사회언어학, 2024)
This study examined the differences in the use of {ne} and {je} in Korean dramas from the 1990s and 2010s in terms of gender and discourse situations. The research focuses on how male and female characters use {ne} and {je} differently in public and private contexts for each era, and how these patterns have changed over time. The findings are summarized as follows. First, in the 1990s, men primarily used {je} in public settings and alternated between {ne} and {je} in private contexts, indicating a context-dependent usage pattern. Women, on the other hand, mainly used {je} in both public and private situations, but {ye} appeared more frequently in public settings, showing that women also adjusted their usage according to the context. Second, in the 2010s, men used both {ne} and {je} regardless of the discourse context, while women predominantly used {ne} across contexts. Third, compared to the 1990s, the use of {ne} in public situations increased for both men and women in the 2010s, indicating a notable change, while no change was observed in private settings.